Attention to brand labels affects, and is affected by, evaluations of product attractiveness - Yang, Xiaozhi; Retzler, Chris; Krajbich, Ian; Ratcliff, Roger; Philiastides, Marios G. (Frontiers in Behavioral Economics, 2024)
When considering whether to purchase consumer products, people consider both the items' attractiveness and their brand labels. Brands may affect the decision process through various mechanisms. For example, brand labels may provide direct support for their paired products, or they may indirectly affect choice outcomes by changing the way that people evaluate and compare their options. To examine these possibilities, we combined computational modeling with an eye-tracking experiment in which subjects made clothing choices with brand labels either present or absent. Subjects' choices were consistent with both the attractiveness of the clothing items and, to a smaller extent, the appeal of the brands. In line with the direct support mechanism, subjects who spent more time looking at the brands were more likely to choose the options with the preferred brands. When a clothing item was more attractive, subjects were more likely to look longer at the associated brand label, but not vice versa. In line with indirect mechanisms, in the presence of brand labels subjects exerted more caution and showed marginally less attentional bias in their choices. This research sheds light on the interplay between gaze and choice in decisions involving brand information, indicating that brands have both direct and indirect influences on choice.